Multifunctionality Urban Green Space. An Analytical Framework and the Case Study of Greenbelt in Frankfurt am Main, Germany. Multifunktionalität öffentlicher Grünräume. Analytischer Rahmen und Fallstudie GrünGürtel Frankfurt am Main, Deutschland. - Wei, Linlin (My University, 2017)
Die Arbeit unterstreicht die Bedeutung der Multifunktionalität in der urbanen Grünraumplanungspraxis und bildet einen analytischen Multifunktionsrahmen für die ganzheitliche Interpretation des Grüngürtels Frankfurt am Main. Basierend auf einer Literaturrecherche zur Entwicklung verwandter Themen, argumentiert die Studie, dass die meisten Komponentenfunktionen der Multifunktionalität eine lange Tradition in der Planungsgeschichte haben und Multifunktionalität eher eine neue holistische Perspektive als ein neuer Begriff ist. Darüber hinaus sollten die Ökosystemleistungen als theoretische Grundlage für die Multifunktionalität gesehen werden, da sie bisher die rationellste und umfassendste Klassifizierung für die Komponentenfunktionen sowie mehrere Analyseansätze bietet. Aufbauend auf der theoretischen Studie wird ein analytischer Rahmen für die Untersuchung des Grüngürtels Frankfurt am Main erstellt und angewendet. Das Gesamtergebnis der Fallstudie zeigt deutlich die Fortschritte und möglichen Richtungen für die zukünftige Entwicklung von Grüngürteln auf.

This research emphasizes the significance of multifunctionality in urban green space planning practice and builds an analytical framework of multifunctionality for the holistic interpretation of the studied case, the Greenbelt Frankfurt am Main. Multifunctionality has been widely used in the context of urban green space planning practice and evaluation in recent years. It is considered as a key characteristic in several contemporary concepts like Green Infrastructure, Ecosystem Services and Landscape Planning. With the spreading of the new concepts and the transition of urban green space planning to a more critical role, the lack of clarification of this term may lead further confusion and misuse. This research aims at the clarification and application of multifunctionality in the context of urban green space planning practice, as a necessary entry point for the future researches on urban green infrastructure planning. Based on literature review on the development of related topics, this study argues that most component functions of multifunctionality have long traditions in planning history and multifunctionality is more about a new holistic perspective instead of a new term; moreover, the ecosystem services should be seen as the theoretical base for multifunctionality because it provides so far the most rational and overall classification for the component functions as well as multiple analyzing approaches; furthermore, the interactions among functions are the unignorable parts of multifunctionality and distinguish it from only multiple functions. Based on the theoretical study, an analytical framework is built and applied on the Greenbelt in Frankfurt am Main, Germany. The methodology combines both semi-quantitative and qualitative approaches and targets on the analyses in both planning process and land use performance status, to discuss how multifunctionality of urban green space is influenced by planning efforts. The results on urban level analyses illustrate that the spatial distribution of functions in reality is quite uneven while the main planning efforts were made without specific focus.
Keywords: Freiraumplanung; Flächennutzung; Freifläche; Öffentliche Grünfläche; Grünflächenplanung; Ökosystem; Stadtökologie; Planungsprozess; Stadtlandschaft; Fallstudie; Grünraumplanung; Grüngürtel; Stadtgrün; Multifunktionalität; Umsetzung; Revitalisierung